Linking entrepreneurial orientation with innovation performance in SMEs; the role of organizational commitment and transformational leadership using smart PLS-SEM - Iqbal, Shuja (2022)
Entrepreneurial orientation has become an enormously significant construct in the innovation studies literature. Predominantly for SMEs, its role has been widely recognized in almost all regional contexts across the globe. The present study is aimed at investigating the effects of entrepreneurial orientation, transformational leadership and organizational commitment on innovation performance. The data for the present study were collected from 1095 employees working at various levels in SMEs. The present study used partial least square structural equation modeling to examine the constructed hypotheses. The findings suggested the significantly positive direct relationships among entrepreneurial orientations, organizational commitment and innovation performance. Besides, organizational commitment positively mediated the relationships between entrepreneurial orientation and innovation performance. Additionally, this study also found the significant moderation of transformational leadership among entrepreneurship orientation and organizational commitment. Leaders of small and medium-sized enterprises should practice entrepreneurial orientation (innovativeness, proactiveness, and risk-taking) and transformation leadership (articulating a compelling vision, focus on goal achievement, and creative problem solving) to enhance the innovation performance of their firms. Moreover, this study provides a robust mechanism for leaders at SMEs to develop strategies for enhancing the willingness of the firms to bring innovation and offer new products and services. The policymakers should enhance the emotional attachment of employees with their firms, sense of moral obligation to remain with the firm which will, in turn, increase the organizational commitment of employees for innovation performance. The study provides empirical evidence to the resource-based view in the context of SMEs. The study delivers solid theoretical and practical implications to experts, leaders and policymakers.